Pengaruh Profitabilitas dan Likuiditas Terhadap Kebijakan Hutang Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2022 - Nurmasita, Sella; Siska, Elmira; Indra, Natal (Jurnal Manajemen Riset Inovasi, 2023)
This study aims to determine the effect of liquidity (CR) and profitability (ROA) on debt policy (DER) in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange. This research was conducted in food and beverage sub-sector companies listed on the Indonesia Stock Exchange with a population of 84 in 2019-2022. The sampling method in this study used a purposive sampling technique so that a sample of 31 companies was obtained. This research is an associative quantitative research. The population in this study is the entire financial statements of the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2019 – 2022. Based on the results of the research conducted, it can be seen that the variables of profitability and liquidity partially have a negative and significant effect on debt policy. Simultaneously the variables of profitability and liquidity and sales growth have a positive and significant effect on debt policy